Belajar Nilai Islami lewat Cerita Rakyat: Menyulam Moral di Era Digital - Nurlaili Hidayatul Baiti; Rachmat Panca Putera (Moral : Jurnal kajian Pendidikan Islam, 2025)
In the digital era, the erosion of moral values among young people has become a pressing challenge for Islamic Religious Education (PAI). Folktales, as part of Indonesia’s cultural heritage, offer universal moral lessons that resonate with Islamic principles. This study investigates the potential of folktales as instructional media for instilling Islamic values while addressing the demands of digital-based learning. A qualitative descriptive method was applied, involving textual analysis of folktales, classroom observations, and interviews with teachers and students. The selected stories Malin Kundang, Bawang Merah Bawang Putih, Timun Mas, and Lake Toba were examined to identify moral values consistent with Qur’anic and prophetic teachings. Data were analyzed using reduction, presentation, and conclusion drawing, supported by triangulation to enhance validity. The results reveal that folktales embody key Islamic values such as filial piety, honesty, patience, courage, and loyalty to promises. Their integration into PAI classes not only increased student attention and emotional engagement but also encouraged deeper moral reflection. Moreover, digital adaptations through animations, videos, and digital storytelling expanded their relevance to contemporary learners, although challenges remain in teachers’ digital literacy and the need for contextual reinterpretation. This study concludes that folktales are more than cultural narratives; they are strategic tools for moral education. By leveraging digital innovation, folktales can reinforce character formation, sustain the relevance of PAI, and prepare Muslim students to be adaptive and value-driven in navigating modern society.